The Influence of Training towards Employee Performance; The Mediating Factor of Teamwork at The Ritz-Carlton Hotel, Bali - Florent, Vicky; Shu, Efin (Institut Pariwisata dan Bisnis Internasional, 2023)
The Ritz-Carlton, Bali, a five-star resort, received guest feedback regarding employee performance and services. The feedback mostly indicated that the services did not meet guest expectations, and guests expressed dissatisfaction with employee performance. The purpose of this research is to find out the influence of training (X) towards employee performance (Y) with teamwork (Z) as the mediating factor at The Ritz-Carlton, Bali. This research uses quantitative method. The population in this research are all employees at The Ritz-Carlton, Bali, with total sample of 134 individuals that were determined using the Slovin formula. All the data results have successfully passed the validity and reliability tests. Furthermore, the results for all data have also met the criteria of both the inner model and outer model tests. The findings regarding path coefficients and P-values demonstrate that training influences employee performance, training influences teamwork, and training influences employee performance through teamwork, signifying that training holds the greatest influence on performance. However, according to the path coefficient, teamwork exhibits a negative influence towards employee performance. To enhance employee performance at The Ritz-Carlton, Bali, the hotel management may want to consider implementing a regular schedule for employee training initiatives to foster collaboration among their colleagues and improve their overall performance.